Answer:
-19
Step-by-step explanation:
For this case we have the following equation of motion:
h (t) = -16t ^ 2 + 90t
Equaling the equation to zero we have:
-16t ^ 2 + 90t = 0
We look for the roots of the polynomial:
(t) (- 16t + 90) = 0
t1 = 0 (initial position)
t2 = 90/16 = 5.625 s (time it reaches the ground again)
Answer:
it will return to the ground in:
t = 5.625 s
You have this man keep doing what u doing
Answer:
![-2\frac{9}{40}](https://tex.z-dn.net/?f=-2%5Cfrac%7B9%7D%7B40%7D)
Step-by-step explanation:
(find common denominator)
![=-\frac{89}{40}](https://tex.z-dn.net/?f=%3D-%5Cfrac%7B89%7D%7B40%7D)
(reduce to simplest form)
Hope this helps :)